Regresja kwantylowa a estymacja VaR - Trzpiot, Grażyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This paper discusses a quantile regression as a model for estimating downside market risk measures - VaR. Firstly, the author presents a problem of quantile regression defined in statistics. Secondly, we made in a few steps applications of this approach to estimate VaR accordingly to different assumptions for time series of returns. The paper also describes a dynamic quantile statistical test. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 465-471